ISOLASI KHAMIR DARI BATANG TANAMAN TEBU DAN IDENTIFIKASINYA BERDASARKAN SEKUENS INTERNAL TRANSCRIBED SPACER - Anggraini, Ika; Ferniah, Rejeki Siti; Kusdiyantini, Endang (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
Isolation of Yeasts from Sugarcane Stems and Their Identification Based on Internal Transcribed Spacer Sequences ABSTRACTFermentative yeasts used in food, health, and energy industries need to be explored to discover their potential. The purpose of this study was to obtain fermentative yeast isolates from sugarcane stems and subsequently to undertake morphological, biochemical, and molecular identification. The isolation of epiphytic and endophytic yeasts was carried out by spread plate method using sugarcane soak water and sugarcane juice on potato dextrose agar (PDA) and yeast-glucose-peptone (YGP) agar media. Morphological identification was based on macroscopic and microscopic observations. Biochemical identification was performed using carbohydrate fermentation and 50%-glucose media tests. Selected isolates were identified molecularly using Internal Transcribed Spacer (ITS). Seven yeast isolates were obtained, of which isolate Ed 1B was selected. Isolate ED 1B was of round colonies, creamy white colour, shiny, embossed, and wavy appearance, ovoid cell shape with a cell diameter of 4.74 µm. It had budding cells, was able to ferment glucose and sucrose (but not lactose), and grew on 50 %-glucose media. Results of BLAST showed that isolates Ed 1B had 99% homology with Kodamaea ohmeri.Keywords: isolation, ITS, molecular identification, Saccharum officinarum L., yeast ABSTRAKKhamir fermentatif yang digunakan dalam industri pangan, kesehatan dan energi perlu dieksplorasi untuk mengetahui potensinya. Tujuan penelitian ini adalah untuk memperoleh isolat khamir fermentatif dari batang tebu dan untuk kemudian diidentifikasi secara morfologi, biokimia dan molekuler. Isolasi khamir epifit dan endofit dilakukan dengan metode cawan sebar dari air rendaman tebu dan jus tebu pada media potato dextrose agar (PDA) dan yeast-glucose-peptone (YGP). Identifikasi morfologi berdasarkan pengamatan makroskopis dan mikroskopis. Identifikasi biokimia menggunakan uji fermentasi karbohidrat dan uji media glukosa 50%. Isolat terpilih diidentifikasi molekuler menggunakan Internal Transcribed Spacer (ITS). Hasil isolasi memperoleh 7 isolat khamir. Satu isolat terpilih (Ed 1B) didapatkan dan memiliki ciri-ciri koloni bulat, putih krem, mengkilap, timbul, bergelombang, bentuk sel ovoid dengan diameter sel 4,74 µm, memiliki budding cell, mampu memfermentasi glukosa dan sukrosa, tidak memfermentasi laktosa, serta tumbuh pada media glukosa 50%. Hasil BLAST menunjukkan bahwa isolat Ed 1B memiliki homologi 99% dengan Kodamaea ohmeri.Kata Kunci: identifikasi molekuler, isolasi, ITS, khamir, Saccharum officinarum L.